Анна Падо. Беседа. Беседа – skutecznie i atrakcyjnie. Издательство: Draco, сс. 130 - Kuca, Zoja (Acta Universitatis Lodziensis. Folia Linguistica Rossica, 2019)
This paper outlines Беседа 1–3 by Anna Pado, a series of Russian language handbooks for students who begin studying Russian as their second language at the upper secondary school (in the Polish educational system). It outlines the main attributes of the series that make it superior to other educational materials available to Polish students. The series helps develop communication skills, improve speech and text composition, teaches accuracy, offers project work, and more.